Norms of Morality as the Foundation for the Development of Legislation on the Digital Economy - E. N. Abramova (Теоретическая и прикладная юриспруденция)
The study is devoted to identifying the importance of moral norms in the formation of a regulatory framework in the digital economy. Objective: to determine the role of moral norms in the era of the digital economy in law. Results: the importance of moral norms as an effective criterion for determining the admissibility and justification of a new legal norm is proved. Moral norms should be used when establishing rules of conduct in connection with digital objects and the user agreement. The law of the digital economy does not need the formation of new principles of ethics or other in connection with the introduction of digital technologies.